New competences to manage urban health: Health City Manager core curriculum - Lenzi, Andrea; Capolongo, Stefano; Ricciardi, Gualtiero; Signorelli, Carlo; Napier, David; Rebecchi, Andrea; Spinato, Chiara (Acta Biomedica Atenei Parmensis, 2020)
A core curriculum is an essential step in development knowledge, competences and abilities and it defines educational content for the specialized area of practice in such a way that it can be delivered to new professional job. The Health City Manager core curriculum defines the strategic aspects of action to improve health in cities through a holistic approach, with regard to the individual, and a multi-sectoral approach, with regard to health promotion policies within the urban context. The Health City Manager core curriculum recognizes that the concept of health is an essential element for the well-being of a society, and this concept does not merely refer to physical survival or to the absence of disease, but includes psychological aspects, natural, environmental, climatic and housing conditions, working, economic, social and cultural life - as defined by the World Health Organization (WHO). The Health City Manager core curriculum considers health not as an “individual good” but as a “common good” that calls all citizens to ethics and to the observance of the rules of civil coexistence, to virtuous behaviours based on mutual respect. The common good is therefore an objective to be pursued by both citizens and mayors and local administrators who must act as guarantors of equitable health ensuring, that the health of the community is considered as an investment and not just as a cost. The role of cities in health promotion in the coming decades will be magnified by the phenomenon of urbanization with a concentration of 70% of the global population on its territory.